Supramolecular nanomedicines through rational design of self-assembling prodrugs. (June 2022) - Wang, Han; Monroe, Maya; Leslie, Faith; Flexner, Charles; Cui, Honggang
Abstract : Advancements in the development of nanomaterials have led to the creation of a plethora of functional constructs as drug delivery vehicles to address many dire medical needs. The emerging prodrug strategy provides an alternative solution to create nanomedicines of extreme simplicity by directly using the therapeutic agents as molecular building blocks. This Review outlines different prodrug-based drug delivery systems, highlights the advantages of the prodrug strategy for therapeutic delivery, and demonstrates how combinations of different functionalities – such as stimuli responsiveness, targeting propensity, and multidrug conjugation – can be incorporated into designed prodrug delivery systems. Furthermore, we discuss the opportunities and challenges facing this rapidly growing field. Highlights: The development of self-assembling prodrugs represents an emerging drug delivery strategy that leverages the assembly potential of therapeutic agents to construct a wide variety of supramolecular nanomedicines. Therapeutic release can be controlled by the chemical stability of the prodrug through the linker design, and also by the supramolecular stability of the nanomedicine that is determined by its critical assembly concentration. Biological epitopes for tumor targeting, specific cell recognition, or intracellular trafficking, can be incorporated as part of the prodrug that contributes to its pharmacokinetic and pharmacodynamic profiles. Prodrug nanoparticles and hydrogels can be used to deliver other therapeutic agents for combination chemotherapy or immunotherapy.